The Automatic Sampling Converter - Kvedaras, V.; Kvedaras, R.; Zaveckas, V. (Elektronika ir Elektrotechnika, 2005)
For today’s measurement automatic sampling converters, without the help of the operator providing the automatic synchronization, measuring duration of a researched time interval and on an output of the converter duration of a researched interval of the set length are necessary. The circuit of the developed automatic converter using the controlled generator with a code by controlled frequencies and phases is investigated. By means of a code changing frequencies of the generator signal, and thus and sampling pulses, automatic synchronization and the set duration of a researched time interval is carried out, and having changed a phase of a target signal of the generator, the time scale of a pause between two researched time intervals will not be transformed. Requirements to a step of reorganization of frequency of recurrence sampling pulses in modes of search of synchronization and tracking are established. Il. 4, bibl. 5 (in Lithuanian; summaries in Lithuanian, English, and Russian.).